Fog computing system for internet of things: Survey (Texas Journal of Engineering and Technology, 2023)
The Internet of Things is one of the most popular topics in the last decade, which has facilitated human tasks and daily tasks. In the IoT system, connected devices generate large-scale data to communicate with each other and perform the necessary tasks, which makes one of the challenges of using the IoT to manage the data generated through it. Cloud-based IoT systems are challenged by high latency, heterogeneity, and large scale. One of the proposed solutions to this problem is to transform data management and analysis by a computational and integrated model by the network called Fog computing. Compared to traditional cloud computing, Fog computing reduces energy consumption and is very suitable for delay-sensitive services with low traffic density, thus making it more efficient to use resources and perform better for bandwidth, energy consumption, and latency. This article investigates the concept of the Fog computing model and its architecture and its features, and then an extensive review of the proposed work on fog computing in the Internet of Things will be done